Moral and Sexual Disgust Suppress Sexual Risk Behaviors among Men Who Have Sex with Men in China - Zhang, Jing; Zheng, Lijun; Zheng, Yong (Frontiers in Psychology, 2017)
ABSTRACT Increasingly more men who have sex with men (MSM) are engaging in sexual risk taking in China in recent years. Given the high rates of HIV infection among MSM in China, it is urgent that we understand the factors that influence MSM’s practice of sexual risk taking. Disgust sensitivity, which elicits a behavioral avoidance response, has the potential to influence risky sexual behavior. The present study examined the relationship between disgust sensitivity and sexual risk behavior among MSM in China. Men (n = 584) who reported having anal intercourse in the previous 6 months were recruited from the Internet. Two indicators of sexual risk behaviors were measured: condom use and the number of sex partners. The results indicated that moral disgust was positively associated with condom use, with MSM who had higher moral disgust being more likely to use condoms than others did. Sexual disgust was positively associated with the number of sex partners, with MSM who had higher sexual disgust having fewer male sex partners than others did. Sexual and moral disgust sensitivity significantly predicted HIV testing. Our study verified that sexual and moral disgust suppressed sexual risk behaviors and promoted HIV testing. Moral and sexual education should be incorporated in future strategies for HIV prevention and encouragement of safe sex behaviors among MSM in China.